Various Bit-Rotation Technique On Key-Symmetric Matrix (International Journal of Engineering and Computer Science, 2015)
Cryptography is one type of very much challenging  methods in today’s technological world for hiding the secret information. Security is the main purpose of the Cryptography. Actually, the main aim of the Cryptography is protecting the data or informations from unauthorized users or hackers. In cryptography, it has two parts: one is Encryption Algorithm and another one is Decryption Algorithm. In this paper, we have proposed a new Encryption Algorithm to encrypt the plain Text to Cipher Text and the Decryption Algorithm to do the reverse. Here we applied various bit-rotation techniques with complement, shifting and transposing on key-symmetric matrix. These operations are simple and easily to implement.